Biogenic synthesis of silver nanoparticles using nicotiana tobaccum leaf extract and study of their antibacterial effect - Prasad, Kumar Suranjit; Pathak, Darshit; Patel, Ankita; Dalwadi, Palak; Prasad, Ram; Patel, Pradip; Selvaraj, Kaliaperumal (African Journal of Biotechnology, 2011)
A green synthesis of silver nanoparticle was carried out using tobacco leaf extract. Synthesized nanoparticles were characterized using UV-Vis absorption spectroscopy, TEM, EDAX, FT-IR and photoluminescence study, respectively. UV-Vis absorption spectroscopy of prepared silver colloidal solution showed absorption maxima at 418 nm. Excitation maximum and emission maximum obtained from photoluminescence study were found at 414 and 576 nm, respectively. TEM analysis showed average particle size of 8 nm, while SAED pattern confirmed the crystalline nature of synthesized nanoparticles. FT-IR analysis indicated the involvement of carboxyl (-C = O), hydroxyl (-OH) and amine (-NH) functional groups of tobacco leaf extract in preparation of silver nanoparticles. EDAX analysis showed proportion of silver (54.55%) among other elements in nanoparticle. Pseudomonas aeruginosa and Escherichia coli DH5 alpha showed highest sensitivity towards silver nanoparticles.
Keywords: FT-IR spectroscopy; photoluminescence; silver nanoparticles; Tobacco; UV-Vis absorption

Biosynthesis of Se nanoparticles and its effect on UV-induced DNA damage - Prasad, Kumar Suranjit; Patel, Hirnee; Patel, Tirtha; Patel, Khusbu; Selvaraj, Kaliaperumal (Colloids and Surfaces B-Biointerfaces, 2013)
This paper reports, an environmentally benign procedure of synthesis and characterizations of selenium nanoparticles and their protective effect against UV-induced DNA damage activities. An aqueous leaf extract of lemon plant was used as a precursor for synthesis of colloidal selenium nanoparticles. Resulting nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX, FT-IR and XRD, respectively. Selenium colloidal solution exhibited an absorption maximum at 395 nm and produced an emission maximum at 525 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, selenium nanoparticles of diameter ranging from (similar to 60 to 80 nm). X-ray diffraction studies showed the formation of 111, 2 0 0 and 220 planes of face-centered cubic (fcc) selenium. EDAX analysis confirmed the presence of selenium in nanosphere. Fourier transformed infrared spectroscopic investigation reveled the involvement of carboxyl (-C=0), hydroxyl (-OH), amine (-NH) functional group of lemon plant extract in preparation of selenium nano particles. MU assay as well single cell gel electrophoresis assay or comet assay revealed that synthesized selenium nanoparticles, caused less cell death of lymphocytes and prevented DNA damage, when cells were exposed to UVB. The fluorescent property of selenium nanopartides can be used as diagnostic agent. Further, their anti DNA damaging property can be investigated as a chemotherapeutic agent in cancer therapy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Comet assay; EDAX; FT-IR; MTT assay; Selenium nanoparticles; UV-vis spectrophotometer

Biogenic synthesis of selenium nanoparticles and their effect on as(III)-induced toxicity on human lymphocytes - Prasad, Kumar Suranjit; Selvaraj, Kaliaperumal (Biological Trace Element Research, 2014)
{A bioreductive capacity of a plant, Terminalia arjuna leaf extract, was utilized for preparation of selenium nanoparticles. The leaf extract worked as good capping as well as stabilizing agent and facilitated the formation of stable colloidal nanoparticles. Resulting nanoparticles were characterized using UV-Vis spectrophotometer, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction analysis (XRD), respectively. The colloidal solution showed the absorption maximum at 390 nm while TEM and selected area electron diffraction (SAED) indicated the formation of polydispersed, crystalline selenium nanoparticles of size raging from 10 to 80 nm. FT-IR analysis suggested the involvement of O-H, N-H
Keywords: Arsenite; Comet assay; EDAX; MTT assay; Selenium nanoparticles; Terminalia arjuna

Defluoridation using biomimetically synthesized nano zirconium chitosan composite: kinetic and equilibrium studies - Prasad, Kumar Suranjit; Amin, Yesha; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2014)
{The present study reports a novel approach for synthesis of Zr nanoparticles using aqueous extract of Aloe vera. Resulting nanoparticles were embedded into chitosan biopolymer and termed as CNZr composite. The composite was subjected to detailed adsorption studies for removal of fluoride from aqueous solution. The synthesized Zr nanoparticles showed UV-vis absorption peak at 420 nm. TEM result showed the formation of polydispersed, nanoparticles ranging from 18 nm to 42 nm. SAED and XRD analysis suggested an fcc (face centered cubic) Zr crystallites. EDAX analysis suggested that Zr was an integral component of synthesized nanoparticles. FT-IR study indicated that functional group like -NH
Keywords: Aloe vera; Chitosan; FT-IR spectroscopy; Sorption; Zirconium nanoparticles

Synthesis of green nano iron particles (GnIP) and their application in adsorptive removal of As(III) and As(V) from aqueous solution - Prasad, Kumar Suranjit; Gandhi, Pooja; Selvaraj, Kaliaperumal (Applied Surface Science, 2014)
{The present study reports a new approach to synthesise nano iron particles using leaf extract of Mint (Mentha spicata L.) plant. The synthesised GnIPs were subjected to detailed adsorption studies for removal of arsenite and arsenate from aqueous solution of defined concentration. Iron nanoparticles synthesised using leaf extract showed UV-vis absorption peaks at 360 and 430 nm. TEM result showed the formation of polydispersed nanoparticles of size ranging from 20 to 45 nm. Nanoparticles were found to have core-shell structure. The planer reflection of selected area electron diffraction (SAED) and XRD analysis suggested that iron particles were crystalline and belonged to fcc (face centred cubic) type. Energy-dispersive X-ray analysis (EDAX) shows that Fe was an integral component of synthesised nanoparticles. The content of Fe in nanoparticles was found to be 40%, in addition to other elements like C (16%), 0 (19%) and Cl (23%). FT-IR study suggested that functional groups like NH
Keywords: Adsorption; Arsenate; Arsenite; Iron nanoparticles; kinetics; M. spicata L.

Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM

Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy

Removal of fluoride from aqueous solution by mesoporous silica nanoparticles functionalized with chitosan derived from mushroom - Srivastava, Anushree; Kumari, Madhu; Ramanathan, Alagappan; Selvaraj, Kaliaperumal; Prasad, Bablu; Prasad, Kumar Suranjit (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
In the present study, chitosan functionalized mesoporous silica nanoparticles have been synthesized. Chitosan derived from an edible mushroom, Agaricus bisporus was used during synthesis of chitosan functionalized silica nanoparticles. The functionalized silica nanoparticles were subjected to fluoride sorption using a batch method which subsequently showed removal efficiency of 95% with maximum sorption capacity, 58.8 mg/g. The characterization of nanoparticles was carried out by SEM, EDAX, XRD and FTIR analysis respectively. EDAX analysis suggested that oxygen, 51.83% and silica 37.24% was main constituent of the functionalized nanomaterials. XRD yielded characteristic diffraction pattern corresponding to the lattice planes (100), (110), (112), (120), (200) and (220) respectively. Sorption data was used to study equilibrium isotherm namely Langmuir and Freundlich model. The adsorption capacity increased with temperature while kinetics studies revealed that the adsorption process followed a pseudo-second-order rate equation. The enthalpy change (Delta H) and entropy change (Delta S) was found to be -31.36 kJmol(-1) and -7.75 Jmol(-1) K-1, showing endothermic and spontaneous nature of the fluoride adsorption. Data suggested that the nature of adsorption belonged to chemisorptions. The overall results suggested that the synthesized nanoparticles showed strong and specific affinity for fluoride and could be excellent adsorbents for defluoridation.
Keywords: Adsorption; Chitosan; EDAX; Fluoride; SEM